Comparing cover crop research in farmer-led and researcher-led experiments in the Western Corn Belt - Koehler-Cole, Katja; Basche, Andrea; Thompson, Laura; Rees, Jennifer (Frontiers in Sustainable Food Systems, 2023)
Cover crops can mitigate soil degradation and nutrient loss and can be used to achieve continuous living cover in cropping systems, although their adoption in the Western Corn Belt of the United States remains low. It is increasingly recognized that cover crop integration into corn (Zea mays L.)-based crop rotations is complex, requiring site and operation specific management. In this review, we compared on-farm, farmer-led field scale trials to researcher-led trials carried out in small plots on University of Nebraska-Lincoln experiment stations. Although there is a range of cover crop research conducted in the state, there is no synthesis of the scope and key results of such efforts. Common cover crop challenges and goals in the state are similar to those reported nationwide; challenges include adequate planting timing, associated costs, and weather, while a top goal of cover crop use is to improve soil health. Farmer-led trials most frequently compared a cover crop to a no-cover crop control, likely reflecting a desire to test a basic design determining site-specific performance. Both researcher-led and farmer-led trials included designs testing cash crop planting timing, while some portion of farmer-led trials tested cover crop seeding rates, which are directly related to reported cover crop challenges. Farmer-led trials were carried out on a greater variety of soils, including sandy soils, whereas sandy soils were absent from researcher-led trials. More than half of farmer-led experiments were conducted on fields with slopes of 6–17% while most researcher-led experiments were conducted on fields with slopes of <1%. Mean cover crop biomass production was 600 kg/ha in farmer-led and 2,000 kg/ha in researcher-led trials. Crop yields were not significantly affected by cover crops in either farmer-led or researcher-led trials. Such comparisons demonstrate that in some instances, cover crop research is addressing challenges, and in some instances, it could be expanded. This synthesis expands our knowledge base in a way that can promote co-learning between different scales of experiments, and ultimately, reduce risks associated with cover crop management and further promote continuous living cover of agricultural landscapes.